The selection for river indicators to assess the ecological status in a campus area - Abu Noh, Safiah; Harun, Nor Zalina; Mansor, Mazlina (IIUM Press, 2017)
The concept of sustainable campus has emerged from the social, economic and environmental impacts due to anthropogenic activities around the world. One of the initiatives of sustainable campus is the application of ecological indicators. The indicators provide information about the current condition and early warning on the possible risks of environmental impacts to the campus environment. However, lack of understanding on the values of natural ecosystem in campus and the lack of proper planning has led to the depletion of natural ecosystem. The study seeks to examine river degradation in IIUM campus and to propose a framework of selecting river indicators towards achieving IIUM as an ecologically sustainable campus. For this purposes, three objectives were formulated, (i) to identify the significance of river indicators in campus physical planning, (ii) to examine the river ecosystem in IIUM campus and the factors that contribute to its depletion, and (iii) to propose a selection process to identify suitable physical indicators to assess IIUM river condition in achieving ecologically sustainable campus. Data were gathered using a qualitative approach involving three methods of data collection namely: (i) document analysis, (ii) semi-structured interview and (iii) site inventory. The finding reveals that the application of river channel morphology indicators is an important basis for physical planning in making a campus ecologically sustainable. Furthermore, it is reported that the sedimentation in the river is caused by anthropogenic activities namely the construction activity, sand mining activity and clogged culvert. Consequently, the physical environment of the river was found to be mostly affected by the anthropogenic activities. Further analysis suggests that the suitable indicators to assess the condition of IIUM River are the river channel morphology indicators such as width, depth, channel pattern and slope ratio. The process of selecting the indicators are carried out based on six criteria of good indicators discussed in this study.